2014
DOI: 10.7243/2053-6623-2-2
|View full text |Cite
|
Sign up to set email alerts
|

Oral health protocol for liver transplant patients

Abstract: Chronic liver disease and cirrhosis were the ninth leading cause of death in Brazil in 2011. Infectious complications are major factors for morbidity and mortality in liver transplant recipients. Oral infection is a cause of systemic infection for both liver transplant candidates and recipients. Liver transplant patients are at high risk of oral infection and preventive measures are mandatory. Oral treatment is feasible to the majority of patients awaiting liver transplantation. However, protocols for oral les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…[ 15 ] This organism can act as a source of invasive and systemic Candida infection with a high mortality rate in the recipients. [ 21 ] C. glabrata is a common fungal pathogen in the oral cavity, causing systemic and mucosal infections, and exhibiting natural resistance to azole antifungal agents. [ 13 ] Our results showed similar anti- Candida growth inhibition effects of L. inermis leaf and unripe Z. spina Christi in comparison with fluconazole in C. albicans .…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] This organism can act as a source of invasive and systemic Candida infection with a high mortality rate in the recipients. [ 21 ] C. glabrata is a common fungal pathogen in the oral cavity, causing systemic and mucosal infections, and exhibiting natural resistance to azole antifungal agents. [ 13 ] Our results showed similar anti- Candida growth inhibition effects of L. inermis leaf and unripe Z. spina Christi in comparison with fluconazole in C. albicans .…”
Section: Discussionmentioning
confidence: 99%
“…These patients often suffer reduced salivary flow, which predisposes them to the onset of periodontal disease and caries. Also, oral indicators are higher in patients with liver cirrhosis or in patients with hepatitis B or C [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The SF-36 has eight health concepts [14]. Some literature reviews [8][9][10][15][16][17] demonstrate that few studies have been conducted in the area of oral health, quality of life, and chronic liver disease in the world, and no study has been conducted in Iran so far.…”
Section: Introductionmentioning
confidence: 99%
“…These patients frequently present reduced salivary flow (7), making them more susceptible to the onset of periodontal diseases and caries. By their turn, such oral manifestations can contribute to the occurrence and worsening of severe complications, such as hepatic encephalopathy (8) and pyogenic liver abscess (9). A systematic review (10) found few published studies about the association between periodontal disease and liver cirrhosis.…”
Section: Introductionmentioning
confidence: 99%